2015
DOI: 10.1111/nph.13503
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interactions between diverged alleles of Early heading date 1 (Ehd1) and Heading date 3a (Hd3a)/ RICE FLOWERING LOCUS T1 (RFT1) control differential heading and contribute to regional adaptation in rice (Oryza sativa)

Abstract: SummaryInitiation of flowering, also called heading, in rice (Oryza sativa) is determined by the florigens encoded by Heading date 3a (Hd3a) and RICE FLOWERING LOCUS T1 (RFT1). Early heading date 1 (Ehd1) regulates Hd3a and RFT1. However, different rice varieties have diverged alleles of Ehd1 and Hd3a/RFT1 and their genetic interactions remain largely unclear.Here we generated three segregating populations for different combinations of diverged Ehd1 and Hd3a/RFT1 alleles, and analyzed their genetic interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(63 citation statements)
references
References 54 publications
2
61
0
Order By: Relevance
“…Homologs of Ehd1 have not been identified in Arabidopsis or other dicot species, but they are present in the genomes of monocots, thus encoding a function not shared by all plants, and that likely evolved after the split between monocots and dicots about 150M years ago [68,69]. The gene works as an upstream transcriptional activator of Hd3a and RFT1 and promotes flowering under SD also in the absence of a functional Hd1 [12,70]. However, its repression under LD is mediated by genes whose homologs are present in Arabidopsis, and function in the regulation of flowering time also in dicot species.…”
Section: Discussionmentioning
confidence: 99%
“…Homologs of Ehd1 have not been identified in Arabidopsis or other dicot species, but they are present in the genomes of monocots, thus encoding a function not shared by all plants, and that likely evolved after the split between monocots and dicots about 150M years ago [68,69]. The gene works as an upstream transcriptional activator of Hd3a and RFT1 and promotes flowering under SD also in the absence of a functional Hd1 [12,70]. However, its repression under LD is mediated by genes whose homologs are present in Arabidopsis, and function in the regulation of flowering time also in dicot species.…”
Section: Discussionmentioning
confidence: 99%
“…However, the identification of Ehd1, Hd3a, and RFT1 as targets of florigen-containing complexes in leaves of rice suggests that one function of these complexes is feedback tuning of the expression of some of its own components. In particular, by reducing transcription of Ehd1, florigen repressor complexes can indirectly limit expression of Hd3a and RFT1, downstream targets of Ehd1 (Doi et al, 2004;Zhao et al, 2015). Since seasonal expression of the rice florigens is transient and is strongly reduced upon completion of the floral transition, a plausible biological role for this autoregulatory loop could be to switch off transcription of the florigens upon floral commitment.…”
Section: The Rice Florigens Act In Leaves To Regulate Their Own Exprementioning
confidence: 99%
“…The complex, originally found to be dimeric based on studies in Arabidopsis, was later demonstrated to contain also a 14-3-3 protein of the Gf14 family (G-box factor 14-3-3) that bridges the interaction between OsFD1 and Hd3a. The resulting ternary complex, named florigen activation complex (FAC), is targeted to the nucleus where it further dimerizes, forming a heterohexameric complex tethered by OsFD1 on target DNA sequences (Zhao et al, 2015;Taoka et al, 2011). Similar interactions take place in many plant species, including tomato (Solanum lycopersicum; Park et al, 2014), potato (Solanum tuberosum; Teo et al, 2017), wheat (Triticum aestivum) and barley (Hordeum vulgare; Li et al, 2015), maize (Zea mays; Danilevskaya et al, 2008), and ½AQ2 hybrid aspen (Tylewicz et al, 2015), suggesting that this molecular module is widely conserved among angiosperms.…”
Section: Both Proteins Share Homology With Flowering Locus T (Ft) Ofmentioning
confidence: 99%
“…Early heading date 1 (Ehd1) is a unique gene that induces the expression of Heading date 3a (Hd3a) and Rice Flowering locus T1 (RFT1), two florigens in rice (Doi et al, 2004;Zhao et al, 2015). Ehd1 merges various upstream flowering signals and acts as a signal integrator.…”
mentioning
confidence: 99%